Posterior Cortical Atrophy: Primary Occipital Variant. (20th December 2022) - Shir, Dror; Graff‐Radford, Jonathan; Machulda, Mary M.; Pham, Nha Trang Thu; Jack, Clifford R.; Lowe, Val J.; Whitwell, Jennifer L; Josephs, Keith A
Abstract: Background: Posterior Cortical Atrophy (PCA) is one of the atypical Alzheimer's Disease (AD) variants, characterized by predominant visuospatial and visuoperceptual deficits, with dorsal and ventral subtypes recognized clinically and radiographically. A third primary occipital (caudal) variant has been suggested. The objective of this study was to determine its demographics, clinical manifestations, and biomarker findings. Method: Fifty‐two PCA patients with positive amyloid PET scans were investigated. Patients underwent neuropsychological assessment, 3T MRI imaging and FDG‐, amyloid‐ and tau‐PET scans. Regional FDG‐PET values were normalized to the pons and represented as z‐scores relative to a control population. Patients were divided into "primary occipital" and "other PCA" subgroups according to FDG‐PET defined criteria, with primary occipital defined as patients in which the z‐scores for occipital subregions were at least one standard deviation lower (i.e., more abnormal) than the z scores in all other brain regions. Global amyloid‐PET, temporoparietal FDG‐PET and temporal tau‐PET regions‐of‐interest (ROI) were calculated. Student's T test and Fisher's exact analyses were used to investigate differences in demographics, clinical findings, and imaging biomarkers across the two groups. Result: Nine patients were classified as primary occipital; primary occipital patients were older (64.8±6.9 versus 59.3±6.8, p=0.034) and had more years of education (17.7±1.7 versus 15.1±2.6, p=0.007) compared to the other PCA patients. Clinical evaluation revealed worse performance for the primary occipital group on the Ishihara test for color perception (p<0.001), while the other PCA patients performed worse on the Western Aphasia Battery (WAB) praxis scale (p=0.005). Overall neuropsychiatric symptom burden as defined by the NPI‐Q was lower in the primary occipital group (p<0.001). The FDG‐PET meta‐ROI (weighted median uptake in angular gyrus, posterior cingulate, and inferior temporal ROIs, normalized to the pons and vermis) was higher in the primary occipital subtype (p=0.006), but no differences were observed in amyloid and tau‐PET. Conclusion: Clinical and biomarker findings suggest primary occipital PCA is characterized by an older age at onset, more color perception dysfunction, less severe ideomotor apraxia and less hypometabolism in temporal‐parietal meta‐ROI compared to more established phenotypes.